Employee protection in mergers and acquisitions - Muvwende, Aven (Institute of Development and Labour Law, 2025)
The acquisition of companies by means of takeovers, or transfers is a frequent occurrence in modem industrialised world. The process of takeover of one company by another, or of amalgamation of one company with another or of merger of one company into group of companies may take place in a variety of specific transactions. However, the law of the individual employment contract has received little attention in these circumstances.